Proliferation and fission of peroxisomes: an update - Schrader, Michael; Islinger, Markus (Biochimica et biophysica acta. Molecular cell research, 2016)
In mammals, peroxisomes perform crucial functions in cellular metabolism, signalling and viral defense which are essential to the health and viability of the organism. In order to achieve this functional versatility peroxisomes dynamically respond to molecular cues triggered by changes in the cellular environment. Such changes elicit a corresponding response in peroxisomes, which manifests itself as a change in peroxisome number, altered enzyme levels and adaptations to the peroxisomal structure. In mammals the generation of new peroxisomes is a complex process which has clear analogies to mitochondria, with both sharing the same division machinery and undergoing a similar division process. How the regulation of this division process is integrated into the cell's response to different stimuli, the signalling pathways and factors involved, remains somewhat unclear. Here, we discuss the mechanism of peroxisomal fission, the contributions of the various division factors and examine the potential impact of post-translational modifications, such as phosphorylation, on the proliferation process. We also summarize the signalling process and highlight the most recent data linking signalling pathways with peroxisome proliferation.